The Association of CYP17A1, CYP19A1, and SHBG Gene Polymorphisms in Polycystic Ovary Syndrome Susceptibility: A Systematic Review and Meta-Analysis - Xing, Chuan; Zhao, Han; Zhang, Jiaqi; He, Bing (Frontiers in Physiology, 2022)
Objective: To elucidate the relationship between CYP17A1/CYP19A1/SHBG gene polymorphisms and PCOS susceptibility. Methods: We searched multiple databases from inception to December 2020 and meta analysis was conducted to elucidate the relationship between gene polymorphisms and PCOS risk. Results: 26 studies were included, comprising 4860 PCOS and 4043 controls. CYP17A1 rs743572 polymorphisms were found to be negatively associated with PCOS risk under dominant model (P=0.017, OR=0.83, 95%CI 0.72-0.97, I2=74.80%, Pheterogeneity=0.000) in the general population while neither CYP19A1 rs2414096 polymorphisms (P=0.578, OR=0.87, 95%CI 0.54-1.41, I2=95.90%, Pheterogeneity=0.000) nor SHBG rs6529 polymorphisms (P=0.752, OR=0.99, 95%CI 0.94-1.05, I2=60.90%, Pheterogeneity=0.012) was associated with PCOS susceptibility under dominant model in the general population. Conclusion: CYP17A1 rs7435721 polymorphisms might be protective factors against PCOS in general populations.